The role of input factors in the lexical development of european Portuguese as a heritage language in Portuguese-German bilingual speakers - Flores, Cristina (2017)
In light of previous research on early bilingualism, this study investigates whether 6–11-year-old child heritage speakers (HSs) of European Portuguese (EP), living in Germany, show patterns of lexical development similar to those of monolingual EP children, both in terms of vocabulary size and of lexical composition. Moreover, it assesses the role of factors related to the quantity and quality of the input in the HSs’ lexical development in EP. Twenty-three bilingual and 21 monolingual children were tested on a semi-spontaneous oral production task. The collected data were used to build a corpus composed of three subcorpora (nouns, verbs, adjectives), which served as a basis for between- and within-group comparisons. Information regarding the HSs’ language experience was collected by means of a parental questionnaire. Results revealed significant between-group differences concerning the total corpus and the subcorpora of nouns and verbs. Within-group comparisons showed that both groups produced significantly more nouns than verbs and more verbs than adjectives. Correlation analyses revealed that the HSs’ lexical knowledge is significantly correlated with the input and output quantity at home as well as with the number of EP-speaking parents. Parents emerge as the key players in the acquisition of EP as a heritage language